Adsorption of Biomineralization Protein Mms6 on Magnetite (Fe3O4) Nanoparticles - Arai, Kosuke; Murata, Satoshi; Wang, Taifeng; Yoshimura, Wataru; Oda-Tokuhisa, Mayumi; Matsunaga, Tadashi; Kisailus, David; Arakaki, Atsushi (International journal of molecular sciences, 2022)
Biomineralization is an elaborate process that controls the deposition of inorganic materials in living organisms with the aid of associated proteins. Magnetotactic bacteria mineralize magnetite (Fe3O4) nanoparticles with finely tuned morphologies in their cells. Mms6, a magnetosome membrane specific (Mms) protein isolated from the surfaces of bacterial magnetite nanoparticles, plays an important role in regulating the magnetite crystal morphology. Although the binding ability of Mms6 to magnetite nanoparticles has been speculated, the interactions between Mms6 and magnetite crystals have not been elucidated thus far. Here, we show a direct adsorption ability of Mms6 on magnetite nanoparticles in vitro. An adsorption isotherm indicates that Mms6 has a high adsorption affinity (Kd = 9.52 µM) to magnetite nanoparticles. In addition, Mms6 also demonstrated adsorption on other inorganic nanoparticles such as titanium oxide, zinc oxide, and hydroxyapatite. Therefore, Mms6 can potentially be utilized for the bioconjugation of functional proteins to inorganic material surfaces to modulate inorganic nanoparticles for biomedical and medicinal applications.